The General Transcription Repressor TaDr1 Is Co-expressed With TaVrn1 and TaFT1 in Bread Wheat Under Drought - Zotova, Lyudmila; Kurishbayev, Akhylbek; Jatayev, Satyvaldy; Goncharov, Nikolay P.; Shamambayeva, Nazgul; Kashapov, Azamat; Nuralov, Arystan; Otemissova, Ainur; Sereda, Sergey; Shvidchenko, Vladimir; Lopato, Sergiy; Schramm, Carly; et al. (Frontiers in Genetics, 2019)
The general transcription repressor, TaDr1 gene, was identified during screening of a wheat SNP database using the Amplifluor-like SNP marker KATU-W62. Together with two genes described earlier, TaDr1A and TaDr1B, they represent a set of three homeologous genes in the wheat genome. Under drought, the total expression profiles of all three genes varied between different bread wheat cultivars. Plants of four high-yielding cultivars exposed to drought showed a 2.0-2.4-fold increase in TaDr1 expression compared to controls. Less strong, but significant 1.3-1.8-fold up-regulation of the TaDr1 transcript levels was observed in four low-yielding cultivars. TaVrn1 and TaFT1, which controls the transition to flowering, revealed similar profiles of expression as TaDr1. Expression levels of all three genes were in good correlation with grain yields of evaluated cultivars growing in the field under water-limited conditions. The results could indicate the involvement of all three genes in the same regulatory pathway, where the general transcription repressor TaDr1 may control expression of TaVrn1 and TaFT1 and, consequently, flowering time. The strength of these genes expression can lead to phenological changes that affect plant productivity and hence explain differences in the adaptation of the examined wheat cultivars to the dry environment of Northern and Central Kazakhstan. The Amplifluor-like SNP marker KATU-W62 used in this work can be applied to the identification of wheat cultivars differing in alleles at the TaDr1 locus and in screening hybrids.